The novel extremely acidophilic, cell-wall-deficient archaeon Cuniculiplasma divulgatum gen. Nov., sp. nov. represents a new family, Cuniculiplasmataceae fam. nov., of the order Thermoplasmatales - Golyshina, Olga V.; Lünsdorf, Heinrich; Kublanov, Ilya V.; Goldenstein, Nadine I.; Hinrichs, Kai Uwe; Golyshin, Peter N. (International Journal of Systematic and Evolutionary Microbiology, 2016)
Two novel cell-wall-less, acidophilic, mesophilic, organotrophic and facultatively anaerobic archaeal strains were isolated from acidic streamers formed on the surfaces of copper-orecontaining sulfidic deposits in south-west Spain and North Wales, UK. Cells of the strains varied from 0.1 to 2 mm in size and were pleomorphic, with a tendency to form filamentous structures. The optimal pH and temperature for growth for both strains were 1.0–1.2 and 37–40 °C, with the optimal substrates for growth being beef extract (3 g l-1) for strain S5T and beef extract with tryptone (3 and 1 g l-1, respectively) for strain PM 4. The lipid composition was dominated by intact polar lipids consisting of a glycerol dibiphytanyl glycerol tetraether (GDGT) core attached to predominantly glycosidic polar headgroups. In addition, free GDGT and small relative amounts of intact and core diether lipids were present. Strains S5T and PM4 possessed mainly menaquinones with minor fractions of thermoplasmaquinones. The DNA G+C content was 37.3 mol% in strain S5T and 37.16 mol% for strain PM4. A similarity matrix of 16S rRNA gene sequences (identical for both strains) showed their affiliation to the order Thermoplasmatales, with 73.9–86.3% identity with sequences from members of the order with validly published names. The average nucleotide identity between genomes of the strains determined in silico was 98.75%, suggesting, together with the 16S rRNA gene-based phylogenetic analysis, that the strains belong to the same species. A novel family, Cuniculiplasmataceae fam. nov., genus Cuniculiplasma gen. nov. and species Cuniculiplasma divulgatum sp. nov. are proposed based on the phylogenetic, chemotaxonomic analyses and physiological properties of the two isolates, S5T and PM4 (=JCM 30641=VKM B-2940). The type strain of Cuniculiplasma divulgatum is S5T (=JCM 30642T=VKM B-2941T).
Created from Fastlane, Scopus look-up